Do health insurances reduce catastrophic health expenditure in China? A systematic evidence synthesis - Li, Furong (PLoS One, 2020)
OBJECTIVE: To examine the association of health insurances on catastrophic health expenditure (CHE), and compares that among different health insurances in the last two decades in China. METHODS: The systematic review was conducted according to the Cochrane Handbook and reported according to PRISMA. We searched English and Chinese literature databases including PubMed, EM base, web of science, CNKI, Wan fang, VIP and CBM (Sino Med) for empirical studies on the association between health insurance and CHE from January 2000 to June 2020. Study selection, data extraction and quality appraisal were conducted by two reviewers. The secular trend of CHE rate and comparisons between population with different health insurances were conducted using meta-analysis, subgroup analysis and meta-regression. RESULTS: A total of 4874 citations were obtained, and finally 30 eligible studies with 633917 participants were included. The overall CHE rate was 13.6% (95% CI: 13.1% - 14.0%) from Jan 2000 to June 2020, 12.8% (95% CI: 12.2% - 13.3%) for people with health insurance compared with 16.2% (95% CI:15.4% - 16.9%) for people without health insurance. For types of insurance, the CHE rate was 13.0% (95% CI: 12.4% - 13.6%) for people with new rural cooperative medical scheme (NCMS), 11.9% (95% CI: 9.3% - 14.5%) for urban employees health insurance (UEBMI), 12.0% (95% CI: 8.3% - 15.6%) for urban residents health insurance (URBMI), and 18.0% (95% CI: - 4.5% - 31.5%) for commercial insurance. However, the CHE rate in China has increased in the past 20 years, even adjusted for other factors. The CHE rate of people with NCMS has increased significantly more than people with UEBMI and URBMI. CONCLUSION: In the past 20 years, the basic health insurance plan has reduce the rate of CHE to a certain extent, but due to the rapid increase in medical costs and the release of health needs in recent years, it masks the role of health insurance. More efforts are needed to control unreasonable medical demand and rising costs.